Therapeutic Effects of Rosemary Leaf Extract on Liver and Kidney Parameters of Rats Treated with Cypermethrin - Somda, Marius K. (مجلة الانبار للعلوم البيطرية)
Background: Cypermethrin, a widely used synthetic pyrethroid insecticide, is known to induce hepatotoxicity and nephrotoxicity through oxidative stress and inflammatory pathways. Rosemary (Rosmarinus officinalis) extract has demonstrated antioxidant and anti-inflammatory properties, suggesting potential therapeutic benefits against pesticide-induced organ damage. Aims and Objectives: This study aimed to evaluate the protective effects of rosemary leaf extract on liver and kidney parameters in rats exposed to cypermethrin. Materials and Methods: Forty male rats (180–220 g) were divided into four groups: control (G1, maize oil), cypermethrin-only (G2, 66.5 mg/kg), and two treatment groups (G3/G4: cypermethrin + 100/200 mg/kg rosemary extract). Treatments were administered orally for six weeks, after which serum levels of AST, ALT, ALP, urea, and creatinine were measured. Results: Cypermethrin significantly elevated liver enzymes (AST, ALT, ALP) and kidney markers (urea, creatinine) in G2 compared to controls (P ≤ 0.05). Co-administration of rosemary extract (G3/G4) dose-dependently reduced these elevations, with G4 (200 mg/kg) showing near-normalization of parameters. Conclusion: Rosemary extract ameliorated cypermethrininduced hepatic and renal dysfunction, likely due to its antioxidant and anti-inflammatory properties, highlighting its potential as a therapeutic adjunct against pesticide toxicity